Conductivity response of amorphous oxide interfaces to pulsed light illumination. (9th April 2019) - Barone, C; Mauro, C; Sambri, A; Scotti di Uccio, U; Pagano, S
Abstract: Two-dimensional electron gases (2DEGs) formed at oxide interfaces show a large variety of functional properties of major physical interest. Here, the peculiar electric transport behavior of the 2DEG formed at the LGO/STO oxide interface is studied under the application of light pulses of different amplitude, duration, and repetition rate, and by varying the sample temperature from 8 to 300 K. The experimental results evidence a persistent photoconductivity, intimately related to the complex physics of this system. These findings suggest the possibility of using the oxide interfaces for advanced applications as, for example, energy conversion or information storage.